Hearing the Other: Communication as Shared Life - James Risser (University of Calgary, 2019)
In the phenomenological tradition, which took root in the first part of the twentieth century, the issue of intersubjectivity became prominent as a way of characterizing social life. But as seen in the work of Edith Stein, for example, this philosophy of intersubjectivity gives prominence to the subject, and as such it leaves open not only the question of the basic character of social life, but also the hermeneutic problem of understanding the other. The focus of my remarks in this paper will explore the way in which Gadamer moves beyond a philosophy of subjectivity in his effort to establish the conditions for communicative understanding. For Gadamer, communicative understanding only occurs through a genuine way of being with another. It requires not just being in relation to the other but a form of participation that amounts to an idea of shared life. Gadamer establishes the precise character of this shared life in relation to his critical encounter with Karl Löwith’s version of the I-Thou relation.